Cross-organ protection of MSC-derived extracellular vesicles in ischemia-reperfusion injury: angiogenic synergy in kidney, brain, and heart - Lai, Zhuhong; Li, Dong; Luo, Caidong; Qiu, Qingyan; Li, Rong; Dai, Min (Frontiers in Cardiovascular Medicine, 2025)
Ischemia-reperfusion injury, marked by transient blood flow disruption followed by tissue reperfusion, constitutes a unifying pathological mechanism across cerebral stroke, myocardial infarction, and acute kidney injury. Hypoxia, a central driver of ischemia-reperfusion injury progression, triggers molecular cascades that simultaneously exacerbate tissue damage and activate compensatory repair mechanisms. Notably, hypoxia-induced angiogenesis and vascular remodeling serve as critical adaptive processes for functional recovery, supporting neuronal plasticity in stroke, myocardial salvage in infarction, and tubular regeneration in renal ischemia-reperfusion injury. While these conditions exhibit organ-specific manifestations, emerging studies underscore conserved regulatory frameworks mediated by extracellular vesicles (EVs) and their molecular cargoes, which orchestrate cross-organ protective responses. In this context, mesenchymal stem cell (MSC)-derived EVs have emerged as potent therapeutic agents for mitigating ischemia-reperfusion injury-related deficits, as evidenced by preclinical and clinical studies. These EVs act as bioactive nanocarriers, delivering cargos that modulate shared pathological pathways-particularly angiogenesis, a linchpin of post-ischemic tissue repair. Accumulating evidence highlights cargos within MSC-EVs (e.g., miRNAs, proteins) as master regulators of vascular regeneration, fine-tuning endothelial proliferation, vessel maturation, and hypoxia adaptation. This review systematically examines the dual roles of MSC-EV-associated cargos in promoting or suppressing angiogenesis across cerebral, cardiac, and renal ischemia-reperfusion injury models. By dissecting their mechanisms in spatiotemporal regulation of vascular signaling networks, we aim to elucidate their translational potential as universal therapeutic targets for multi-organ ischemia-reperfusion injury management.